Portal Vein Thrombosis following Total Colectomy due to Colonic Inertia: A Case Report and Evaluation of Risk Factors - Mohammad Bagher Jahantab; Saadat Mehrabi; Vahid Salehi; Lotfolah Abedini; Mohammad Javad Yavari Barhaghtalab (Case Reports in Hematology)
The portal vein could be occluded by blood clots partially or completely causing portal vein thrombosis (PVT). The acute episode may be asymptomatic or manifested by abdominal pain, increasing body temperature, and unspecific dyspeptic symptoms. The main causes of PVT are categorized into local, acquired, and genetic thrombophilic factors. To our knowledge, this is the 2nd recognized case of PVT  following colectomy for colonic inertia successfully treated with an effective anticoagulation therapy. The patient received unfractionated heparin as soon the diagnosis was implemented. The patient was a 34-year-old lady with chief complaint of severe abdominal pain, nausea, vomiting, and anorexia 10 days after the first hospital admission for subtotal colectomy due to colonic inertia. Spiral abdominal CT  scan with intravenous (IV) contrast showed thrombosis in main portal vein with its extension to right and left intrahepatic branches. Our case showed that we should keep in mind PVT in patients who present with upper gastrointestinal symptoms several days after a major surgery (open colectomy) as a risk factor and oral contraceptive pills (OCP) usage, postpregnancy, and immobility as other risk factors, that the protein C, S, and FVL deficiencies were secondary, and that the PVT can be managed by low molecular weight heparin plus oral warfarin therapy in the continue.